Dual Functionalized Lactococcus lactis Shows Tumor Antigen Targeting and Cytokine Binding in Vitro - Zahirović, Abida; Plavec, Tina Vida; Berlec, Aleš (Frontiers in Bioengineering and Biotechnology, 2022)
Pro-inflammatory cytokines play an important role in the development and progression of colorectal cancer (CRC). Tumor-targeting bacteria that can capture pro-inflammatory cytokines in the tumor microenvironment and thus block their tumor-promoting effects might provide clinical benefits in inflammation-associated CRC. The aim of this study was to develop bacteria with dual functionality for selective delivery of cytokine-binding proteins to the tumor by targeting specific receptors on cancer cells. We engineered a model lactic acid bacterium, Lactococcus lactis, to co-display on its surface a protein ligand for tumor antigens (EpCAM-binding affitin; HER2-binding affibody) and a ligand for pro-inflammatory cytokines (IL-8-binding evasin; IL-6-binding affibody). Genes that encoded protein binders were cloned into a lactococcal dual promoter plasmid, and protein co-expression was confirmed by Western blotting. To assess the removal of IL-8 and IL-6 by the engineered bacteria, we established inflammatory cell models by stimulating cytokine secretion in human colon adenocarcinoma cells (Caco-2; HT-29) and monocyte-like cells (THP-1; U-937). The engineered L. lactis removed considerable amounts of IL-8 from the supernatant of Caco-2 and HT-29 cells, and depleted IL-6 from the supernatant of THP-1 and U-937 cells as determined by ELISA. The tumor targeting properties of the engineered bacteria were evaluated in human embryonic kidney epithelial cells HEK293 transfected to overexpress EpCAM or HER2 receptors. Fluorescence microscopy revealed that the engineered L. lactis specifically adhered to transfected HEK293 cells, where the EpCAM-targeting bacteria exhibited greater adhesion efficiency than the HER2-targeting bacteria. These results confirm the concept that L. lactis can be efficiently modified to display two proteins simultaneously on their surface: a tumor antigen binder and a cytokine binder. Both proteins remain biologically active and provide the bacteria with tumor antigen targeting and cytokine binding ability.